The predicaments of child victims of crime seeking justice in Ethiopia: a double victimization by the justice process - Woldemariam, Getachew Assefa (Afrika Focus, 2011)
This article presents an account of a legal system that has fundamentally failed Ethiopia ́s young and vulnerable citizens. The Ethiopian justice process has permitted the subjection of child victims to cycles of traumatisation during investigation, prosecution and trial phases of cases in which they are involved. Ethiopia does not have laws that require the special treatment of children who are victims or witnesses of crime. It has neither rules of criminal procedure nor evidence that direct the conduct of criminal proceedings involving child victims. This article will show that although the Ethiopian Constitution incorporates principles such as the consideration of ‘the best interests of the child’, the realization of this principle for the Ethiopian child victim of crime remains illusory due to the absence of detailed rules that guide and compel the justice process to that effect. Based on empirical data, the article argues further that although ad hoc initiatives to introduce victims to a child-friendly justice process exist in a limited number of urban areas, these initiatives do not reach the vast majority of child victims around the country who continue to be further victimized by the justice process. Key words: Ethiopia, child victims, justice process, court, double victimization